Tooth-supported overdenture vs stud retained overdenture: a case report - Hazira M. Yusof (Indonesian Journal of Prosthodontic, 2022)
Overdenture can preserve alveolar bone while providing support and stability to the prosthesis. This case report describes a treatment of a tooth-supported partial overdenture for the upper and lower stud retained overdenture. This method provides an alternative solution to the conventional partial denture and implant retained overdenture. This treatment is a simple and cost-effective, which provides the patient with a highly retentive, stable denture with improved masticatory performance.